Does Dynamic Capability Lead to Sustainable Innovation Performance in Smes? - Yuli Liestyana; Tri Wahyuningsih; Yekti Utami; Hadi Oetomo; Tugiyo Tugiyo (Journal of International Conference Proceedings, 2025)
These researchers analyzed micro, small, and medium enterprises (MSMEs) in Bantul Regency, Indonesia, to determine whether dynamic capabilities have a positive impact on sustainable innovation performance.  In general, MSMEs in Indonesia play a crucial role in sustaining a resilient economy, which has proven to be able to withstand uncertain conditions. In developing countries such as Indonesia, MSMEs are expected to effectively manage both internal and external resources to achieve a sustainable competitive advantage. In this study, data were collected from 176 MSMEs that met the criteria of possessing dynamic capabilities in four main aspects: sensing capabilities, learning capabilities, integrating capabilities, and coordinating capabilities. The respondents in this study were managers or owners of MSMEs. Using regression analysis, the researchers found that these four aspects had a positive effect on the sustainable innovation performance of MSMEs in Bantul Regency. Thus, it has been proven that managing all aspects of dynamic capabilities is a strategic step to improve MSME performance, especially in terms of sustainable innovation.